+0  
 
0
148
1
avatar+589 

1. What is (f−g)(x)?

 

f(x)=x4−x2+9

g(x)=x3+3x2+12

 

 

2. What is (f⋅g)(x)?

 

f(x)=x2+2x−6

g(x)=x4+3

 

 

3. What is (f+g)(x)?

 

f(x)=x3−x

g(x)=x3+2x2−10

jbouyer  Feb 13, 2018
 #1
avatar+89775 
+2

1. What is (f−g)(x)?

 

f(x)=x^4−x^2+9

g(x)=x^3+3x^2+12

 

f - g   =   [ x^4 - x^2 + 9 ]  - [ x^3 + 3x^2 + 12 ]  =

 

x^4  -- x^3  - x^2 + 3x^2  + 9  -  12   =

 

x^4 - x^3   +  2x^2  -  3 

 

2. What is (f⋅g)(x)?

 

f(x)=x^2+2x−6

g(x)=x^4+3

 

f*g   =  ( x^2 + 2x + 6)  ( x^4 + 3)  =

 

         x^2  +  2x  + 6        multiply each term on top by 3  and then by x^4      

x                 x^4  + 3

       ____________

         3x^2  + 6x + 18

+    x^6  + 2x^5 + 6x^4

     ________________

 

x^6  + 2x^5 + 6x^4  + 3x^2 + 6x + 18  

 

 

3. What is (f+g)(x)?

 

f(x)=x^3−x

g(x)=x^3+2x^2−10   

 

f +  g   =   [ x^3 - x ]  +  [ x^3 + 2x^2  - 10  ]  =   2x^3 + 2x^2 - x  - 10

 

 

 

cool cool cool

CPhill  Feb 13, 2018

10 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.